Low Carbon Development in Support of Improving Environmental Quality in Nigeria - Michele, Okocha (International Journal Papier Advance and Scientific Review, 2023)
The importance of technology advancements in Low Carbon Development (LCD) and their significant effects on both environmental sustainability and economic growth are highlighted in this abstract. The transformational role of innovations is highlighted by examining them in several sectors, such as waste management, carbon capture, energy efficiency, renewable energy, and sustainable transportation. In addition to reducing carbon emissions, these inventions support the development of a green economy, job creation, and economic resilience. According to the abstract, as countries—including Nigeria—adopt technological solutions, they are paving the way for a peaceful coexistence of environmental sustainability and economic growth.